2020
DOI: 10.1002/fes3.221
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of photosynthesis‐related genes regulated by alternate wetting and drying irrigation in flag leaves of rice

Abstract: Alternate wetting and drying (AWD) irrigation has been widely used to replace continuous flooding (CF), which does not result in yield loss while improving water productivity. However, it is still unexplored as to how this agricultural practice would affect gene expression to control plant physiology. In this study, we found that photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), chlorophyll (Chl) content, and leaf water potential (Lwp) significantly decreased while abscisic acid (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 65 publications
1
9
1
Order By: Relevance
“…8 ). Our findings showed that the following genes were expressed to a greater extent in DJ123 in comparison to those in IR64 under the HPS treatment: (1) Os01g0110100 ( PHO1;1 ), which encodes a protein involved in transferring Pi from root to shoot 38 and maintaining Pi homeostasis 39 , 40 , (2) Os02g0168800 encodes a porphobilinogen deaminase 41 . Porphobilinogen deaminase has been reported to promote vegetative and reproductive development 42 , (3) Os04g0326201 encodes a glycosyltransferase 43 .…”
Section: Discussionmentioning
confidence: 90%
“…8 ). Our findings showed that the following genes were expressed to a greater extent in DJ123 in comparison to those in IR64 under the HPS treatment: (1) Os01g0110100 ( PHO1;1 ), which encodes a protein involved in transferring Pi from root to shoot 38 and maintaining Pi homeostasis 39 , 40 , (2) Os02g0168800 encodes a porphobilinogen deaminase 41 . Porphobilinogen deaminase has been reported to promote vegetative and reproductive development 42 , (3) Os04g0326201 encodes a glycosyltransferase 43 .…”
Section: Discussionmentioning
confidence: 90%
“…The results of this study showed that the chloroplasts, plastids, thylakoids and other cellular components directly related to photosynthesis of maize would change significantly under the stable soil water content controlled by NPI. This is also a possible reason for the increase of photosynthetic rate, dry matter accumulation and yield of maize [34].…”
Section: Plos Onementioning
confidence: 99%
“…In addition, atpB, which is directly related to the formation of ATP, was significantly up-regulated. This helps the corns to convert light energy into ATP for plant use and hence may be genes directly related to the increase in corn yield [34]. Therefore, it is deduced that the enhancement of photosynthetic capacity and energy metabolism of maize is the main physiological and molecular mechanism in response to stable soil water content.…”
Section: Plos Onementioning
confidence: 99%
“… 63 Large arrays of light-harvesting complex (LHC) are assembled as the peripheral components of PSII and PSI, designated LHCII and LHCI, respectively. 64 65 The most important function of the LHC is to capture the solar energy and transfer its energy to the reaction center. 66 67 The transcriptome results of this study indicated that the most significantly enriched KEGG pathway of mulberry under flooding stress was photosynthesis-antenna protein (map00196).…”
Section: Discussionmentioning
confidence: 99%